Staff perception of the implementation, enablers and barriers to pediatric intensive care unit diary writing: A qualitative study. (April 2023) - Sansone, Vincenza; Cancani, Federica; Cecchetti, Corrado; Rossi, Angela; Gagliardi, Chiara; Di Nardo, Matteo; Satta, Tiziana; De Ranieri, Cristiana; Dall'Oglio, Immacolata; Tiozzo, Emanuela; Gawronski, Orsola
Abstract: Objectives: To explore how the multi-professional pediatric intensive care unit staff experienced the implementation of the diary. Research Methodology/Design: Qualitative study using the implementation research approach. Setting: a six-bed pediatric intensive care unit at a large Italian tertiary care pediatric hospital, treating patients with acute conditions from the Emergency Department or hospital wards. Main outcome measures: Healthcare providers' experiences of the implementation of the diaries. Data was collected by focus groups and interviews and thematic analysis was performed. Findings: Three focus groups and four interviews with staff were conducted after the implementation of thediaries from August 2020 to June 2021. Staff describe an initial disbelief towards the effectiveness of diaries followed by an increasing perception of their relevance for parents' emotional expression through shared narration. Diaries are reported as a beneficial communication tool between the family, the child, and health care providers, increasing staff understanding of parents' experiences of their child's admission and parents' sense of the care received by their child. For staff, barriers for diary writing were logistics, lack of time, limited sense of ownership, fear of legal retaliation and fear of emotional labor. Conclusion: Health care providers perceived diaries as beneficial for parents and the healthcare team, potentially supporting their partnership as recommended by Family Centered Care models. The enablers and barriers that emerged for diary writing can support the development of implementation strategies to prevent the reported challenges to diary writing in the healthcare team, enhancing their uptake in the pediatric intensive care unit setting.